Parkinson’s disease beyond the brain: implications for treatments - Malekian Naeini, Setareh; Lopez, Marc Danzell; Fraser, Paul E.; Tandon, Anurag (Frontiers in Aging Neuroscience, 2025)
The presence of α-synuclein pathology in peripheral nervous system neurons is linked to early prodromal, non-motor symptoms in a segment of Parkinson’s disease (PD) patients referred to as “body-first.” These features of the disease suggest a convergence of environmental, genetic, immune and age-related factors within the enteric nervous system as initiating triggers of disease. This review explores the changes in the gut microbiome and intestinal permeability that may drive systemic inflammation and precede neurodegeneration in PD. The pathways leading to the formation of α-synuclein aggregates are explored as well as their role in transneuronal propagation and the spreading of pathology within the brain. Lastly, advances in systemic gene therapy that could be used to target multiple PD-affected organs following systemic injection are highlighted. By integrating insights from molecular biology and clinical research, it may be possible to shed light on the multifactorial etiology of PD and the interconnectedness of the gut and brain, which could lead to novel diagnostic and therapeutic strategies.